CESAREAN HYSTERECTOMY IN THE NATIONAL HOSPITAL GUILLERMO ALMENARA. LIMA, PERU - García, Fernando (2015)
Objective: To determine incidence and results of cesarean-hysterectomy from 1991 through 1998. DESIGN: Obstetrical Service, Guillermo Almenara National Hospital. RESULTS: There were 30851 deliveries, 8746 by cesarean section, incidence 28,3%. Cesarean-hysterectomies represented 0,3% of all cesarean sections or an incidence of 0,94 per 1000 deliveries. Average age was 34,6 years old, 551,7% older women, 20,7 great multiparae, 20,7% nulliparae and 3,6 average parity. Preterm deliveries predominated and previous cesarean section represented, 34,5%. Indications for cesarean section were abruptio placentae, bleeding placenta previa, severe preeclampsia, acute fetal distress, deflection, 2 or 3 previous cesarean sections, prolonged pregnancy, myomatosis, and in situ cervical carcinoma. Indications for hysterectomy were placenta accreta uterine atony, myomatosis, Couvelaire uterus, chorioamnionitis, uterine rupture, and in situ carcinoma. Average intervention duration was 2 hours and 28 minutes, and 3,6 packed globules blood transfusion were used. Intraoperative complications were vesical hematoma, vesical laceration, omentum laceration, difficult hysterorrhaphy due to myomas, pelvic infundibulum hematoma, and coagulopathy Postoperative complications were anemia, infections, vesicocutaneous fistula, and pulmonary thromboembolism. Emergency sections differed with elective in longer surgical time, blood loss, and percentage of patients transfused (p<0,05). Average hospitalization time was 10 days (4-62) days. Maternal mortality 0. Newborns: 9 fetal deaths and 20 live newborns. Patients follow-up was satisfactory. CONCLUSIONS: All gynecologists should dominate surgical technique and indications of cesarean-hysterectomy, because any day the life of a patient can be saved it is important go have available a blood bank and an Intensive Care Unit to obtain good results